GAMBARAN SEL EPITEL PADA LESI PAYUDARA DILABORATORIUM PATOLOGI ANATOMI UPT RSUD DELI SERDANG LUBUK PAKAM - ., Kartini; Krisdianilo, Visensius; Sumantri, Bambang; Sidabutar, Rimayani (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
The breast is an organ that grows as a tissue bulge that is first seen at 7 to 8 weeks after conception. Each breast consists of 12 to 20 tubuloalveolar gland lobules. Each lobule consists of cells consisting of cube epithelial cells and myoepithelial cells that surround the lumen. Lesions in the breast can originate from a connective tissue or from epithelial cells that develop continuously. Some types of epithelial cell traces in breast lesions include fibroadenoma, tumor filoides, papillomas, and papillary carcinoma, and breast carcinoma. This study aims to determine the description of epithelial cells in breast lesions in the Anatomical Pathology Laboratory of UPT Deli Serdang Lubuk Pakam Hospital Period 2018 - 2019. The research was conducted descriptively using the Fine Needle Aspiration Biopsy (FNAB) examination method. The study was conducted using secondary obtained from the medical record of the Anatomical Pathology Laboratory of UPT Deli Serdang Lubuk Pakam Hospital about the description of epithelial cells in breast lesions. The results showed that there were 6 epithelial cell features in breast lesions in the Anatomy Pathology Laboratory of UPT Deli Serdang Hospital. The six epithelial cell features include mammary aberans, mammary adenoma fibrio, mammary dysplasia, mammary multiple fibroadenoma, mammary ductal hyperplasia and mammary carcinoma. From a total of 30 study samples obtained 14 epithelial cells in the form of mammary adenoma fibrio (46.67%). Description of epithelial cells in the form of mammary aberans as many as 7 people (23.33%). For depictions of epithelial cells in the form of mammary carcinoma by 6 people (20%). While the epithelial picture in the form of mammary dysplasia, multiple fibroadenoma mammary and mammary ductal hyperplasia each as much as 1 person (3.33%).